PROJECT-BASED LEARNING BERBANTUAN E-LEARNING: PENGARUHNYA TERHADAP HASIL BELAJAR - Mohammad Salehudin (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
The purpose of this research is to find out the effect of PBL assisted by e-learning on the learning outcomes of understanding concepts, the effect of self-efficacy on the learning outcomes of conceptual understanding, and the effect of PBL assisted by e-learning and self-efficacy together (simultaneously) on the learning outcomes of conceptual understanding. students in following the current lecture process increasingly rely on information technology where one of them is in obtaining lecturing material to achieve high concept understanding learning outcomes. So the support of learning models using ICT e-learning assistance as well as the readiness of students, seft-efficacy owned by students in the following lectures is the basis of this research. This research uses a quantitative approach, a sample of 38 respondents from IAIN FTIK students in Samarinda, the data collected were analyzed with multiple regression. The results of the study there is the effect of PBL assisted by e-learning on the learning outcomes of understanding concepts, there is the effect of self-efficacy on the learning outcomes of concept understanding proven to be significant, and the influence between PBL assisted by e-learning and self-efficacy together (simultaneously) on the learning outcomes of understanding concept. Influence is supported by the strength of the learning model, the power of e-learning (google classroom), class interaction and group collaboration, material and media as well as the environment which influence and significantly influence the learning outcomes of concept understanding, because both the PBL and Self-Efficacy variables have advantages to be applied in e-learning assisted learning, according to the current era of ICT development.